2012
DOI: 10.1186/1472-6963-12-19
|View full text |Cite
|
Sign up to set email alerts
|

Summarizing activity limitations in children with chronic illnesses living in the community: a measurement study of scales using supplemented interRAI items

Abstract: BackgroundTo test the validity and reliability of scales intended to measure activity limitations faced by children with chronic illnesses living in the community. The scales were based on information provided by caregivers to service program personnel almost exclusively trained as social workers. The items used to measure activity limitations were interRAI items supplemented so that they were more applicable to activity limitations in children with chronic illnesses. In addition, these analyses may shed light… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 29 publications
0
36
0
Order By: Relevance
“…The ChYMH builds a comprehensive picture of individuals' mental health needs, over all functioning, and areas of risk to inform care planning for clients. Rigorous reliability and validity studies have been conducted across the family of interRAI instruments, displaying strong psychometric properties for adults (Burrows et al, 2000;Martin et al, 2007;Morris et al, 2000., Perlman and, as well as children and youth (e.g., Phillips et al, 2012;Phillips and Hawes, 2015). Inter-rater reliability of the interRAI instruments were assessed and the average agreement was 83% for all interRAI mental health items (Hirdes et al, 2003;Hirdes et al, 2008).…”
Section: Methodsmentioning
confidence: 98%
“…The ChYMH builds a comprehensive picture of individuals' mental health needs, over all functioning, and areas of risk to inform care planning for clients. Rigorous reliability and validity studies have been conducted across the family of interRAI instruments, displaying strong psychometric properties for adults (Burrows et al, 2000;Martin et al, 2007;Morris et al, 2000., Perlman and, as well as children and youth (e.g., Phillips et al, 2012;Phillips and Hawes, 2015). Inter-rater reliability of the interRAI instruments were assessed and the average agreement was 83% for all interRAI mental health items (Hirdes et al, 2003;Hirdes et al, 2008).…”
Section: Methodsmentioning
confidence: 98%
“…Numerous studies have found items and scales embedded in the ChYMH to have strong psychometric properties (Phillips et al, 2012;Phillips & Hawes, 2015;Stewart, Currie, Arbeau, Leschied, & Kerry, 2015;Stewart & Hamza, 2017). The sample analyzed in this study consisted of 2038 children and adolescents aged 8-18 years (M = 12.49; SD = 2.88).…”
Section: Participantsmentioning
confidence: 99%
“…Exampling a build of generic questionnaire, a study [19] exposed to physical limitations as a general factor for several chronic diseases and concluded that the information collected from the professionals and caregivers constitute a solid foundation for building an individualized treatment plan with a view to improve the health of children, in view of the limitations of each, plus the ability to integrate health information throughout the course of life of these patients.…”
Section: Discussionmentioning
confidence: 99%
“…The synthesis build of the selected studies in the review show that the motivation to develop an instrument or quiz in the theme of chronical is strictly linked to factors, as: handling of a specific disease such as diabetes [6,7,8], sickle cell anemia [9,10], asthma [7,11,12], chronic kidney disease [13], Cystic fibrosis [14]; children and/or adolescents family inclusion in the validation process or as subject of the instrument application [6,10,15,16,17]; measurement of subjective dimensions of life experience with chronic disease such as: quality of life [7,13], satisfaction with care [17], chronic pain experience [18] as well as the limitations to develop common activities [19]. The use of statistical measures as tools to support the validity, reliability and reproducibility of instruments built was present in all studies.…”
Section: Discussionmentioning
confidence: 99%